5(-6x+6)=-90

Simple and best practice solution for 5(-6x+6)=-90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(-6x+6)=-90 equation:


Simplifying
5(-6x + 6) = -90

Reorder the terms:
5(6 + -6x) = -90
(6 * 5 + -6x * 5) = -90
(30 + -30x) = -90

Solving
30 + -30x = -90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-30' to each side of the equation.
30 + -30 + -30x = -90 + -30

Combine like terms: 30 + -30 = 0
0 + -30x = -90 + -30
-30x = -90 + -30

Combine like terms: -90 + -30 = -120
-30x = -120

Divide each side by '-30'.
x = 4

Simplifying
x = 4

See similar equations:

| X-10-4x=20 | | x-58=370 | | 13=18-h | | 13-6x=4x-77 | | 3(x-3)=-9+2x | | 2y+8=3y+8 | | r-109=65 | | -5(7x+2)=-115 | | 2y+3-6=5y+12 | | 13-6x=4x-7 | | m-79=12 | | u-(-3)=12-(-7) | | 4y-7-2=5y+1 | | 2w+2(2w+2)=30 | | 5x-5=3(2x-3) | | 1+5x+4x=-44 | | 2(5x+1)=9(x+1) | | 1(-u)=14 | | a-.6=-.7 | | 2x-3=-11-2x-4 | | 4(4-3x)=16 | | 1(-6)=14 | | 6+5x+3-x=-5+5x+6-2x | | x-2=6-3x+4 | | 6x+0.8(2x-0.1)=151.92 | | x-4=3/4 | | 2(x-4)-5x=19 | | 5x+2x=30 | | 3x-5+1=-2x+9 | | 8x^2-67x-1251=0 | | (5u+1)(3-u)=0 | | A+6=-12 |

Equations solver categories